The political philosophy of G.A. Cohen : back to socialist basics - Vrousalis, Nicholas, 1980- (Bloomsbury research in political philosophy., 2015)
"Gerald Allan Cohen was Chichele Professor of Social and Political Theory at All Souls College, Oxford for 23 years and is considered one of the most influential political philosophers of the past quarter-century. He died in 2009. The Political Philosophy of G.A. Cohen is the first full-length study of Cohen's highly influential thinking and method in political philosophy covering a range of fundamental topics such as equality, freedom and fraternity and his views on Marx, Nozick and Rawlsian concepts. Nicholas Vrousalis brings together the diverse strands of argument in Cohen's political thought and critically reconstructs them in the context of contemporary debates in political, economic, and social theory. This reconstruction will highlight common threads running through Cohen's numerous contributions to contemporary philosophy, without underrating certain inevitable tensions between them"--